AB1254 Subclinical atherosclerosis in patients with psoriatic arthritis evaluated by "ultrasonic biopsy". (23rd January 2014) - Teixeira, F.; Peixoto, D.; Bogas, M.; Afonso, C.; Araújo, D.
Abstract : Background: Increased cardiovascular morbility and mortality has been observed in several inflammatory rheumatic diseases, namely, rheumatoid arthritis and systemic lupus erythematosus The chronic inflammatory state in these diseases may contribute to accelerated atherosclerosis. ``Ultrasonic biopsy" (U-B) is a described noninvasive screening technique to detect early atherosclerotic plaques and arterial wall changes. Objectives: To evaluate the prevalence of subclinical atherosclerosis in patients with Psoriatic Arthritis, examining carotid and femoral arteries and to identify early clinical and biologic markers for these changes in this population. Methods: Consecutive PsA patients who fulfilled the CASPAR criteria who were followed at our Rheumatology departmentbwere recruited. Traditional risk factors, biological inflammatory parameters and disease activity scores were checked. We studied 69 patients (39 women and 30 men), with a median age of 53 years (range 23-80yr) and a median disease duration of 96 months (range 18-552months). All patients underwent U-B study of left and right carotid (CA) and femoral artery (FA). The UB features were classified and scored as follows: Class A, normal (score 0); Class B, interface disruption (score 2); class C, intima-media (I-M) granulation (score 4); Class D, plaque without hemodynamic disturbance (score 6); Class E, stenotic plaque (score 8); and Class F, plaque with symptoms (score 10). Results: Thirty-three (49%)of the 69 patients had at least a lesion in 1 of the 4 vessels tested (Classe C, D e F), these, 12 (36%) had lesion in 4 vessels. The AF was involved in 27 patients but the CA in only 20 patients. The presence of carotid plaque(classes D-F) correlated significantly with disease duration, LDL and triglyceride levels. Diabetes and hypertension were associated with the presence of plaques (classes D-F). Mean C-reactive protein washigher in classes D-F compared to the class A-B. Conclusions: This study evaluates both carotid and femoral arteries in psoriatic arthritis patients looking for subclinical atherosclerosis. The results Our study demonstrates show that patients with PsA may have an increased prevalence of subclinical atherosclerosis. Femoral artery evaluation should be performed and complement the more frequent carotid study as it may show additional information about the atherosclerotic state of the patient. Special attention and strict control of atherosclerotic risk factors in patients with PsA is warranted to prevent future cardiovascular events. Disclosure of Interest: None Declared